Beliefs About Sexual Intimate Partner Violence Perpetration Among Adolescents in South Africa. Issue 3 (February 2021) - Pöllänen, Katri; de Vries, Hein; Mathews, Catherine; Schneider, Francine; de Vries, Petrus J.
Sexual intimate partner violence (IPV) is a public health problem worldwide. Research regarding beliefs about perpetrating sexual IPV is, however, limited. This study investigated attitudes, social influence, and self-efficacy beliefs and intentions toward perpetrating sexual IPV among Grade 8 adolescents ( M age = 13.73, SD = 1.04) in the Western Cape Province of South Africa. The study sample was taken from the baseline data of the Promoting sexual and reproductive health among adolescents in Southern and Eastern Africa (PREPARE) study, a cluster-randomized controlled trial. Young adolescents ( N = 2, 199), from 42 randomly selected high schools, participated in the study and answered a paper-and-pencil questionnaire. Multivariate ANOVA were conducted to assess differences in beliefs and intention toward perpetrating sexual IPV between boys and girls, and between perpetrators and nonperpetrators. Results showed that boys were more frequently perpetrators (11.3% vs. 3.2%) and victims (13.6% vs. 6.4%) of sexual IPV than girls. Boys' attitudes toward perpetrating sexual IPV were more supportive than girls'. Boys perceived their social network to be more likely to think that putting pressure on a boyfriend or girlfriend to have sex is okay, and boys had a lower self-efficacy to refrain from pressuring a boyfriend or girlfriend to have sex compared with girls. Both boys and girls, who have perpetrated sexual IPV, had more tolerant attitude, social influence, and self-efficacy beliefs toward sexual IPV perpetration, compared with nonperpetrators. Intention not to perpetrate sexual IPV did not differ between boys and girls, or between perpetrators and nonperpetrators. Our findings suggest that interventions should address attitude and social influence beliefs regarding sexual IPV perpetration. More attention should be given to sexual IPV perpetration among boys. Given that sexual IPV victimization and perpetration are significantly linked, prevention of sexual IPV perpetration seems to be of utmost importance.